2022
DOI: 10.1177/10422587211069374
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial Opportunities as Responsibility

Abstract: Entrepreneurship involves cooperative efforts in which multiple stakeholders and resources are brought together to develop a valuable product or service. Accordingly, one key process through which entrepreneurs make progress exploiting their opportunities is by identifying, selecting, enrolling, and coordinating a network of stakeholders. However, although there is a widespread realization that bringing new ventures to life requires multiple stakeholders, precious little academic research has taken a holistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…A power lens might also provide new insights into studies on entrepreneurial networks. While previous research has recognized the development of entrepreneurial opportunities requires support and engagement from various stakeholders (Bosse et al, 2022 ), highlighting the role of supportive entrepreneurial network partners, such as family, friends, and business partners (Hoyte et al, 2019 ), viewing networks as a potential resource to be cultivated may gloss over underlying power dynamics. The study of power considers harmful actors.…”
Section: Discussionmentioning
confidence: 99%
“…A power lens might also provide new insights into studies on entrepreneurial networks. While previous research has recognized the development of entrepreneurial opportunities requires support and engagement from various stakeholders (Bosse et al, 2022 ), highlighting the role of supportive entrepreneurial network partners, such as family, friends, and business partners (Hoyte et al, 2019 ), viewing networks as a potential resource to be cultivated may gloss over underlying power dynamics. The study of power considers harmful actors.…”
Section: Discussionmentioning
confidence: 99%
“…Based on other reports, seeking opportunities and responsibilities from the theory of cultural values was also necessary for the formulation of green entrepreneurship, besides the unrealistic consideration of only desires and intentions. Furthermore, some previous literature confirmed that the development of entrepreneurial opportunities required the support and involvement of multiple parties, as well as various partners, friends, family, businesses, and stakeholders (Hoyte et al, 2019;Bosse et al, 2022). Therefore, this study aims to evaluate the roles of GESI (Gender Equity and Social Inclusion) and institutions as drivers of green entrepreneurship and sustainable development goals (SDGs).…”
Section: Literature Reviewmentioning
confidence: 98%
“…Thus, entrepreneurial initiatives start an entrepreneur's commitment to making a difference by thinking through an idea's strategic details. An important element of this process is initiating the selling of the idea to important stakeholders (De Clercq et al, 2011) by creating a coalition of organisational members who can support the idea (Bosse et al, 2022;Soomro et al, 2020). In organisations like HEIs, entrepreneurial initiatives represent the individual-level expression of organisational capabilities (Mahringer and Renzl, 2018).…”
Section: Entrepreneurial Behaviourmentioning
confidence: 99%
“…Fit or misfit influences employee behaviour, especially regarding workplace adjustments (Vleugels et al, 2022) brought about by significant changes in the workplace, such as a pandemic (Cao et al, 2022). Bosse et al (2022) assert that the entrepreneurial behaviour of exploiting opportunities is conditioned by the entrepreneur's network of workplace relations. This is because entrepreneurship entails cooperative action among concerned interests working harmoniously to achieve a clearly defined objective.…”
Section: Leader-subordinate Fit and Entrepreneurial Behaviourmentioning
confidence: 99%